Identification of SSTR5 Gene Polymorphisms and Their Association With Growth Traits in Hulun Buir Sheep - Li, Xue; Ding, Ning; Zhang, Zhichao; Tian, Dehong; Han, Buying; Liu, Dehui; Liu, Sijia; Tian, Fei; Fu, Dejun; Song, Xiaoliang; Zhao, Kai (Frontiers in Genetics, 2022)
The aim of this study was to locate SSTR5 polymorphisms and evaluate their association with growth traits in Hulun Buir sheep. The study followed 884 Hulun Buir sheep from birth to 16 months of age, which were born in the same pasture and in the same year, and a consistent grazing management strategy was maintained. The birth weight (BRW) wea recorded, and body weight (BW), body height (BH), body length (BL), chest circumference (ChC), chest depth (ChD), chest width (ChW), hip width (HW), and cannon circumference (CaC) were measured at 4 and 9 months of age. BW, BH, BL, ChD, HW, and CaC were also recorded at16 months of age. Based on the growth traits, we selected 233 individuals as our experimental animals. Sanger sequencing was performed, and seven single nucleotide polymorphisms. (SNPs) were identified. Association analyses of the SNPs and the growth traits were then conducted. Seven SNPs of the SSTR5 exhibite moderate polymorphism (0.25＜PIC＜0.5) and were consistent with Hard–Weinberg equilibrium. SNP7(T989C, rs601836309) caused a change in amino acid sequences, while others did not. The genotypes of SNP1(C186T, s400914340) were significantly associated with BW, ChW, and ChC at 4 months of age and with HW at 9 months of age (P＜0.05), These genotypes were also extremely significantly associated with CaC at 4 months of age (P＜0.01). The genotypes of SNP7 exhibited significantly associated with ChW and CaC at 4 and 9 months of age, repectively. Moreover, the genotypes of SNP3 (T384C, rs413380618)) and SNP4 (T537C, rs605867745) were significantly associated with CaC at 9 months of age (P＜0.05). A linkage disequilibrium was observed among the seven SNPs, with five haplotypes. However, these haplotypes were not associated with growth traits at different ages. In conclusion, SNP1, SNP3, SNP4, and SNP7 may serve as molecular markers for the growth traits of Hulun Buir sheep.